Yoga pant nation : a novel - Gelman, Laurie (Henry Holt and Company, 2021)
"The hilarious, irreverent Jen Dixon is class mom-again-for her son's fifth grade year, and a class bully, spin-teacher training, and her irresistible granddaughter keep her on her toes and perpetually in yoga pants"--